Spontaneous blood pressure oscillations in mechanically ventilated patients with sepsis. Issue 2 (April 2016) - Berg, Ronan M.G.; Plovsing, Ronni R.; Greve, Anders M.; Christiansen, Claus B.; Toksvang, Linea N.; Holstein-Rathlou, Niels-Henrik; Møller, Kirsten
Abstract : Objective: In the present hypothesis-generating study, we investigated whether spontaneous blood pressure oscillations are suppressed to lower frequencies, and whether abolished oscillations are associated with an adverse outcome in mechanically ventilated patients with sepsis. Methods: We retrospectively subjected invasive steady-state blood pressure recordings from 65 mechanically ventilated patients with sepsis to spectral analysis. Modified spectral bands were visually identified by plotting spectral power against frequency. Results: Modified middle-frequency and low-frequency (MF′ and LF′) oscillations were absent in 9% and 22% of the patients, respectively. In patients in whom spontaneous blood pressure oscillations were preserved, the MF′ oscillations occurred at 0.021 Hz (median, interquartile range 0.013–0.030), whereas the LF′ oscillations occurred at 0.009 Hz (median, interquartile range 0.006–0.010). The absence of LF′ oscillations was associated with a higher 30-day mortality [50 vs. 18%, hazard ratio, 3.6 (95% confidence interval: 1.4–9.8), P =0.01]. Conclusion: Spontaneous blood pressure oscillations in mechanically ventilated septic patients may be suppressed to lower frequencies than previously reported for spontaneously breathing, healthy humans. Patients in whom the resultant changes in blood pressure (MF′ and LF′ oscillations) are abolished may have a higher risk of an adverse outcome. This may reflect suppression of the pressor area in the brainstem with subsequent sympathetic dysfunction.